İstanbul Da Zemin Yapısının Konut Fiyatlarına Olan Etkisi - Varlıker, Kazım (Fen Bilimleri Enstitüsü, 2015)
Bu çalışmada, İstanbul’daki zemin yapısının konut fiyatlarına ne derecede etkili olduğu incelenmiştir. Geçmişte yapılan araştırmalara bakıldığında bu konunun hem gelişmiş hem de gelişmekte olan ülkelerde yeterince incelenmediği görülmüştür. İstanbul’un her bölgesinde zemin yapısı detaylı bir şekilde incelenerek depreme dayanıklı ve dayanıksız bölgeler tespit edilmiştir. İstanbul’un 37 bölgesinde toplam 1445 konut fiyatı ve alan araştırması yapılarak 2004 yılı İstanbul ortalama konut fiyatı ve birim fiyatları hesaplanmıştır. Her ilçe ve bölgenin zemin yapısı, nüfus yoğunluğu, merkeze olan uzaklık ve gelir parametreleri regresyon analizinin stepwise yöntemi ile incelenmiştir ve sadece gelir unsurunun konut fiyatlarına etkisi olduğu sonucu ortaya çıkmaktadır. Yapılan analizlerde Anadolu Yakası’nın zemin yapısının Avrupa Yakası’na oranla daha sağlam olduğu ancak konut fiyatı olarak daha ucuz olduğu görülmektedir. İstanbul nüfusunun yaklaşık %40 lık bölümü zemini sağlam olmayan konutlarda yaşamakta ve bu bölümünün çoğunluğu Avrupa bölgesinin güney kesimi oluşturmaktadır.

In this study the issue that how much the structure of earth in Istanbul effects the housing prices, is investigated. According to the researches made in the past, it is seen that this case has not been explored enough in either less-developed counties or in the developed countries. In every region of Istanbul the structure of the earth is ascertained with every details and the durable and non-durable areas are determined. 1445 researches for housing prices ve areas have been made in the 37 region of Istanbul and the average housing prices and unit prices regarding 2004 are estimated. The structure of the earth, population density, the proximity to the center and the revenue parameters of every districts and regions are investigated with stepwise method of regression analysis and the results indicate that only the revenue factor has effects on housing prices. In the analysis made, it is seen that the structure of the earth in Asian part is more stronger than European part and the housing prices concerning Asian part is more cheaper than the prices which belong to European part. % 40 of the population of Istanbul has been living in the residences which have not a durable structure of earth and most of the % 40 of the population are consist of the south part of European region.
The Effects Of The Structure Of Earth On Housing Prices In Istanbul
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2005
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2005
Keywords: Regresyon Analizi; Stepwise Yöntemi; Regression Analysis; Stepwise Method